(untitled) (Global Journal of Science Frontier Research, 2022)
The article starts from the natural phenomenon of sparks in the stone tip, analyzes the essence of frictional heat generation, and deduces the theory of pressure heat generation. Geocentric, geothermal, and solar source issues are explained.